2019
DOI: 10.1007/s11116-019-10061-3
|View full text |Cite
|
Sign up to set email alerts
|

The bicycle-train travellers in the Netherlands: personal profiles and travel choices

Abstract: The Netherlands seems to exhibit the unique conditions that allow cycling on the country level instead of only the city level. Moreover, the national transit system seemingly provides one crucial condition: citizens use the train and cycling systems in an integrated manner, with combined bicycle-train transport recently demonstrating strong growth. Relatively little is known about bicycle-train users, i.e. the people who combine the bicycle and the train in a single trip. In this paper, we investigate their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…The connecting lines between the left and right side provide an indication of the relative size of various access-egress mode combinations: as can be seen, the combination of cycling (access) and walking (egress) is the most common. In agreement with previous research (Jonkeren et al 2019), bike use is markedly higher on the access than on the egress side (86% vs. 35%). On the access side, the majority of respondents simply use their own regular bicycle (73%), with a much smaller percentage using, e-bikes (7%), folding bikes (5%), bikesharing (< 1%) or OV-fiets (< 1%).…”
Section: Sociodemographic and Bike-train Trip Characteristicssupporting
confidence: 93%
See 3 more Smart Citations
“…The connecting lines between the left and right side provide an indication of the relative size of various access-egress mode combinations: as can be seen, the combination of cycling (access) and walking (egress) is the most common. In agreement with previous research (Jonkeren et al 2019), bike use is markedly higher on the access than on the egress side (86% vs. 35%). On the access side, the majority of respondents simply use their own regular bicycle (73%), with a much smaller percentage using, e-bikes (7%), folding bikes (5%), bikesharing (< 1%) or OV-fiets (< 1%).…”
Section: Sociodemographic and Bike-train Trip Characteristicssupporting
confidence: 93%
“…Our sample is balanced in terms of gender, but is significantly younger, more educated and has a higher household income than the Dutch average. Such results are largely in line with those of previous studies (Jonkeren et al 2019;Shelat, Huisman, and van Oort 2018), which also found that bike-train travellers tend to be highly educated, with a large proportion of full-time professionals with high incomes, as well as university and school students. In the case of our survey, 61% of respondents worked for an external employer, while 22% were studying or attending school (the rest were either self-employed or not engaged in paid employment).…”
Section: Sociodemographic and Bike-train Trip Characteristicssupporting
confidence: 92%
See 2 more Smart Citations
“…Bicycletransit combines the advantages of speed and accessibility of (particularly higher level) transit with the flexibility and reliability of the bicycle. Recent publications have highlighted the potential of the marginalised and little researched bicycletransit combination (Jonkeren et al 2019;Kager et al 2016;KiM 2016b;Scheltema 2012). This paper aims to provide new knowledge on the bicycle-transit combination.…”
Section: Introductionmentioning
confidence: 99%